Calochaete gen. nov. (Cyanobacteria, Nostocales), a new cyanobacterial type from the “páramo” zone in Costa Rica - Hauer, Tomáš; Bohunická, Markéta; Mühlsteinová, Radka (Phytotaxa, 2013)
A new tapered and false branched morphotype of filamentous heterocytous cyanobacterium was isolated from soil material collected on a massif of Chirripó Mountain, Costa Rica. The strain was analyzed morphologically and a sequence of its 16S rRNA gene was compared with available 16S rDNA sequences of organisms with similar morphology, especially those with heteropolar tapering filaments. Phylogenetic analyses revealed that the strain was significantly different from Rivulariaceae, but was closely related to several strains designated as Tolypothrix. However, according to the original descriptions in the literature, members of the genus Tolypothrix possess only very slightly tapering filaments. With regard to all these differences, we decided to describe a new genus—Calochaete gen. nov. with type species C. cimrmanii.